1976
DOI: 10.1111/j.1469-8137.1976.tb01501.x
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Mycorrhiza in the Ericaceae

Abstract: SUMMARY Mycorrhizal and non‐mycorrhizal plants of Vaccinium macrocarpon were grown in a controlled environment for 12 weeks on sand supplied with five different concentrations of ammonium nitrogen in a logarithmically increasing series ranging from 1.0 to 56.0 parts/106. All plants received a full complement of other mineral elements essential to growth. Interactions between the effects of mycorrhizal infection and nitrogen concentration were studied through the calculation of various growth‐functions. With in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Ericoid mycorrhizae also form less readily when P and N are abundantly supplied (Morrison, 1957;Burgeff, 1961;Stribley and Read, 1976), but Morrison reported that very high applications of P to Pernettya macrostigma stunted root growth, resulting in atypical but intense infection.…”
Section: A Nutrientsmentioning
confidence: 96%
“…Ericoid mycorrhizae also form less readily when P and N are abundantly supplied (Morrison, 1957;Burgeff, 1961;Stribley and Read, 1976), but Morrison reported that very high applications of P to Pernettya macrostigma stunted root growth, resulting in atypical but intense infection.…”
Section: A Nutrientsmentioning
confidence: 96%
“…Most of the information concerning the physiology of ericoid mycorrhizae has been obtained using plants infected with known mycorrhizal fungi under aseptic or axenic conditions (Pearson and Read, 1973b;Stribley and Read, 1975, 1976, 1980Bradley, Burt and Read, 1981). However, before extrapolating results to the field situation it is necessary to ensure that the mycorrhizae synthesized under controlled conditions are morphologically comparable to the natural associations.…”
Section: Introductionmentioning
confidence: 99%
“…Mycorrhizal infection of the plants resulted in a further increase of uptake at intermediate levels of nitrogen (2-7, 7-5, and 20-5 fig N g'^) but not at 1 or 56 fig N g~^ in sand. Plant growth and concentration of N in the tissues was increased in mycorrhizal plantŝ t 2-7 and 7-5/tg N g"^ (Stribley and Read, 1976). Uptake of phosphate by •Tiycorrhizal onions (Sanders and Tinker, 1973;Sanders et al, 1977) and subter-ranean clover (Smith, Nicholas and Smith, 1979) has been measured on the basis of root length (inflow: moles P absorbed per unit root length per unit time, Brewster and Tinker, 1972) and is considerably greater than uptake into uninfected plants in the soils used but the influence of different levels of phosphate was not studied in these experiments.…”
Section: Introductionmentioning
confidence: 99%